2022
DOI: 10.5114/ceh.2022.118594
|View full text |Cite
|
Sign up to set email alerts
|

Association between hypothyroidism and liver fibrosis risk: a systematic review and meta-analysis

Abstract: Aim of the study: Non-alcoholic fatty liver disease (NAFLD), which encompasses a wide variety of liver pathology, is now the most common chronic liver disease worldwide. The presence of hypothyroidism has been linked to the development of NAFLD. However, its correlation with liver fibrosis, an important clinical entity in NAFLD, is less clear. We aimed to summarize the association between hypothyroidism and liver fibrosis risk. Material and methods:We conducted a search of PubMed and ProQuest from inception to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The thyroid axis has profound effects on hepatic energy metabolism, including hepatic lipogenesis and fatty acid oxidation; the liver receives signals from thyroid hormones through activation of thyroid hormone receptors while it has also receptors for TSH, both of which alter hepatic metabolism 45,46 . A consistent line of evidence supports the notion that, compared to euthyroid subjects, both individuals with subclinical and overt hypothyroidism are at higher risk for developing and progressing to steatohepatitis and significant fibrosis 4,7–9,47,48 . One study yielded negative findings.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The thyroid axis has profound effects on hepatic energy metabolism, including hepatic lipogenesis and fatty acid oxidation; the liver receives signals from thyroid hormones through activation of thyroid hormone receptors while it has also receptors for TSH, both of which alter hepatic metabolism 45,46 . A consistent line of evidence supports the notion that, compared to euthyroid subjects, both individuals with subclinical and overt hypothyroidism are at higher risk for developing and progressing to steatohepatitis and significant fibrosis 4,7–9,47,48 . One study yielded negative findings.…”
Section: Discussionmentioning
confidence: 89%
“…45,46 A consistent line of evidence supports the notion that, compared to euthyroid subjects, both individuals with subclinical and overt hypothyroidism are at higher risk for developing and progressing to steatohepatitis and significant fibrosis. 4,[7][8][9]47,48 One study yielded negative findings. Possibly owing to several reasons including failure to handle statistical heterogeneity due to differences in the populations enrolled, definitions of hypothyroidism, methods used to check thyroid hormone profile and study designs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This notion has universally been accepted by subsequent studies [17,18]. In parallel, strong epidemiological evidence has indicated that hypothyroidism is also tightly associated with the development and fibrotic progression of NAFLD and NASH [19][20][21][22]. This association has recently been found to be sex-specific and mediated by adipokines/mitokines [23].…”
Section: What Has Nash To Do With Thyroid?mentioning
confidence: 85%
“…HSCs are the predominant precursor cells of liver myofibroblasts and upon activation, by TGF-β, fibrogenic myofibroblasts up-regulate production and deposition of α-smooth muscle actin and extracellular matrix proteins, the most abundant one being type I collagen. Likewise, experimental studies have shown that hypothyroidism can induce up-regulation of collagen type 1 gene expression, causing subsequent fibrosis [ [13] , [14] , [15] , [16] ].…”
Section: Introductionmentioning
confidence: 99%